Uudenlaiseen Kelan työhönkuntoutukseen? : viiden kuntoutusmallin arvioinnin tuloksia - Hinkka, Katariina, 1955-; Aalto, Liisi, 1960-; Toikka, Tuula (Helsinki : Kelan tutkimusosasto, 2015)
Ny form av arbetslivsinriktad rehabilitering som ordnas av FPA? : resultat av en utvärdering av fem rehabiliteringsmodeller.
New for of rehabilitation into work arranged by Kela? : results of an assessment of five rehabilitation models.
Sammandrag: Ny form av arbetslivsinriktad rehabilitering som ordnas av FPA? : resultat av en utvärdering av fem rehabiliteringsmodeller.
Abstract: New form of rehabilitation into work arranged by Kela? : results of an assessment of five rehabilitation models.
New for of rehabilitation into work arranged by Kela? : results of an assessment of five rehabilitation models.
Ny form av arbetslivsinriktad rehabilitering som ordnas av FPA? : resultat av en utvärdering av fem rehabiliteringsmodeller.
Ny form av arbetslivsinriktad rehabilitering som ordnas av FPA? : resultat av en utvärdering av fem rehabiliteringsmodeller.
New for of rehabilitation into work arranged by Kela? : results of an assessment of five rehabilitation models.
Työhönkuntoutuksen kehittämishanke.
Julkaistu myös verkkoaineistona.
Keywords: Rehabilitation, Vocational; Rehabilitation, Vocational -- methods; Rehabilitation -- methods; Outcome and Process Assessment, Health Care; Program Evaluation; Work; kuntoutus; ammatillinen kuntoutus; kuntoutuslaitokset; työterveys; mallit (mallintaminen); työikäiset; työssä jatkaminen; työkyky; arviointitutkimus; monitahoarviointi; työvalmennus; menetelmät; työ; rehabilitering (vård); yrkesinriktad rehabilitering; rehabiliteringsinrättningar; arbetshälsa; modeller (alster); arbetsträning; personer i arbetsför ålder; fortsatt förvärvsarbete; arbetsförmåga; evalueringsforskning; mångsidig utvärdering; metoder; arbete